A novel Burkholderia vietnamiensis strain for biodegradation of residual tylosin antibiotic in fermentation solid waste. (2015) - Ma, Yu-Long; Wang, Yan; Sun, Rui-Zhu
A large amount of fermentation solid waste (FSW) has been generated during the course of tylosin production. This FSW is difficult to be treated and reused because of tylosin residue. In this study, a novel strain TS1 was isolated and identified as Burkholderia vietnamiensis. This isolate exhibited a strong ability to degrade tylosin, and almost 100% of 200 mg kg −1 tylosin was biodegraded after seven days of incubation. Medium pH and temperature had some influences on the biodegradation capacity of strain TS1. The favourable biodegrading conditions were at pH 7.0 and 30-35°C. The behaviour of tylosin degradation followed a first-order kinetic, and the half-lives were 1.54 to 1.70 days when the initial concentrations of tylosin were from 50 mg kg −1 to 400 mg kg −1 . These findings suggest that strain TS1 can effectively degrade tylosin residue in FSW and may be used for biotreatment of antibiotic solid waste containing tylosin residue.